2022
DOI: 10.1186/s12913-022-07601-6
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance coverage and timely antenatal care attendance in sub-Saharan Africa

Abstract: Introduction Out-of-pocket payments for healthcare remain a significant health financing challenge in sub-Saharan Africa (SSA), preventing women from using maternal health services. There is a paucity of empirical literature on the influence of health insurance coverage on the timeliness of antenatal care (ANC) attendance in low- and middle-income countries. In this study, we examined the association between health insurance coverage and timely ANC attendance among pregnant women in SSA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
3
16
0
1
Order By: Relevance
“…We also found that women with health insurance coverage had a higher likelihood of utilizing quality ANC as compared to their counterparts with no health insurance coverage. This affirms the findings of Dadjo, Ahinkorah and Yaya [ 34 ] and Aboagye et al [ 35 ] that also found health insurance coverage has a significant association with the utilization of ANC. This could be attributed to the fact that health insurance eliminates the financial barriers that could have prevented women from seeking quality ANC services.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that women with health insurance coverage had a higher likelihood of utilizing quality ANC as compared to their counterparts with no health insurance coverage. This affirms the findings of Dadjo, Ahinkorah and Yaya [ 34 ] and Aboagye et al [ 35 ] that also found health insurance coverage has a significant association with the utilization of ANC. This could be attributed to the fact that health insurance eliminates the financial barriers that could have prevented women from seeking quality ANC services.…”
Section: Discussionsupporting
confidence: 91%
“…Women who had health insurance coverage were 1.64 times more likely to complete all 11 MNCH care interventions along with the CoC as compared to their colleagues who had no health insurance coverage. Often, women miss out on MNCH care intervention due to out-of-pocket-payment that usually lead to catastrophic health expenditure [ 6 ]. As such, health insurance becomes the intervention that allows them to go through the CoC while minimizing or completely avoiding out-of-pocket payments.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it is known from the literature that SSA accounts for almost 90% of the global burden of maternal mortality [5]. This high burden of maternal and child mortality in SSA has been linked to several preventable factors including low antenatal care (ANC) utilisation as well as low uptake of postnatal care (PNC), skilled attendant delivery, and health facility delivery [3,6]. Moreover, evidence suggests that easy accessibility to maternal and child healthcare is associated with significantly lower odds of child and maternal mortalities [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher wealth index provides women with autonomy and control over resources. Hence, empowering women to take decisions to utilise skilled ANC services [ 22 ]. This affirms our findings that women who consider getting money needed for treatment as not a big problem have higher likelihood of utilising ANC services from skilled providers as compared to those who consider that as a big problem.…”
Section: Discussionmentioning
confidence: 99%